Self-management of patients with tracheostomy in the home setting: a scoping review - Sandra Weidlich; Jens Pfeiffer; Christiane Kugler (SpringerOpen, 2023)
Abstract Purpose The aim of this study was to create a model of patient-centered outcomes with respect to self-management tasks and skills of patients with a tracheostomy in their home setting. Methods A scoping review using four search engines was undertaken (Medline, CINAHL, PsycINFO, Cochrane Library) to identify studies relevant to this issue and published since 2000. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statements for Scoping Reviews (PRISMA-ScR), the Joanna Briggs Institute (JBI) approach of conducting and reporting a scoping review, and the Participants, Concept, Context (PCC) scheme were employed. The following elements of the framework synthesis study data were screened, and presented based on the self-management model of Lorig and Holman. Results 34 publications from 17 countries met the criteria for study inclusion: 24 quantitative, 8 qualitative and 2 mixed methods designs. Regarding the dimensions of self-management, 28 articles reported on "managing the therapeutic regimen", 27 articles discussed "managing role and behavior changes", and 16 articles explored "managing emotions". A model of self-management of patients with tracheostomy was developed, which placed the patient in the center, since it is this individual who is completing the tasks and carrying out his or her skill sets. Conclusion This scoping review represents the first comprehensive overview and modeling of the complex self-management tasks and skills required of patients with tracheostomy in their home setting. The theoretical model can serve as a cornerstone for empirical intervention studies to better support this patient-centered outcome for this population in the future.